Stress Indicators to Pre-Slaughter Transportation of Broiler Chickens Fed Diets Supplemented with a Synbiotic - Ghareeb, K.; Bohm, J. (International Journal of Poultry Science, 2009)
There is a growing interest concerning the welfare problems associated with harvesting, transportation and pre-slaughter handling of broilers. Transportation is a multifactor process associated with a variety of stressors which may covertly reduce welfare. Plasma corticosterone is elevated following a road which is consistent with the post-transport increase of heterophil: lymphocyte ratios (H/L ratios). Plasma corticosterone was compared with H/L ratio responses to various stressors and the latter was the better indicator of stress in poultry. In the present study, stress responses were evaluated in broiler chickens fed for 5 weeks a synbiotic Biomin® IMBO (a combination of Enterococcus faecium), a pre-biotic (derived from chicory) and immune modulating substances (derived from sea algae), with a dose of 1 kg/ ton of the starter diets and 0.5 kg/ton of the grower diets). The birds were subjected to 80 km transport journey (90 min approximately). Heterophil (H) counts, Lymphocyte (L) counts and Heterophil to Lymphocyte (H/L) ratios were determined immediately on arrival and at 24 h following bird’s transport. The H/L ratios decreased after 24 h from arrival from transport journey by about 17 % for birds fed synbiotic BIOMIN IMBO compared with controls. However, a non significant increase in L counts and a non significant decrease in H counts and H/L ratios at 24 h following bird’s transport for birds fed BIOMIN IMBO compared with controls. In conclusion, feeding of BIOMIN IMBO relatively modulates the stress indicator of transported birds and relatively enhances tolerance to stress after pre-slaughter handling and transportation.